Shared Perspectives Of Spiritual Blindness And Deadness In D.h. Lawrence’s The Blind Man And James Joyce’s The Dead - Hedroug, Souad Sara (The Journal of Studies in Language, Culture, and Society, 2025)
Modernist literature frequently explores themes of psychological and emotional stagnation, reflecting the anxieties of an era marked by rapid social and cultural change. However, while much research has examined individual portrayals of alienation and existential paralysis in modernist fiction, fewer studies have investigated how different authors employ distinct metaphors—such as death and blindness—to critique the limitations of human perception and emotional growth. Addressing this gap, this study conducts a comparative qualitative analysis of James Joyce’s The Dead and D.H. Lawrence’s The Blind Man to explore their shared theme of spiritual deadness and its implications for human relationships and self-awareness. This study seeks to answer the following research questions: (1) How do Joyce and Lawrence use the motifs of death and blindness, respectively, to represent spiritual deadness? (2) In what ways do both texts offer moments of reversal, where the dead regain life and the blind acquire a form of sight? (3) How do these literary representations critique modern life and its failure to provide genuine emotional or spiritual fulfilment? Through a comparative interpretive analysis, this study closely examines the protagonists’ internal and external worlds, demonstrating how Joyce and Lawrence not only depict spiritual paralysis but also introduce dimensions of renewal. By exploring the tensions between spiritual deadness and aliveness, this research highlights how both authors expose the limitations of modern existence, where seemingly living and sighted individuals struggle to achieve true emotional or spiritual awakening.